Heterotrophic Cultivation of Cyanobacteria: Study of Effect of Exogenous Sources of Organic Carbon, Absolute Amount of Nutrients, and Stirring Speed on Biomass and Lipid Productivity - Meireles dos Santos, Aline; Vieira, Karem Rodrigues; Basso Sartori, Rafaela; Meireles dos Santos, Alberto; Queiroz, Maria Isabel; Queiroz Zepka, Leila; Jacob-Lopes, Eduardo (Frontiers in Bioengineering and Biotechnology, 2017)
The production of bioproducts from cyanobacteria with techno-economic feasibility is a challenge to these biotechnological processes. The choice of low cost raw materials is of great importance for the overall economy of bioprocesses, as they represent a significant percentage in the final cost of the product. The objective of this work was to study the operational parameters of cultivation (exogenous sources of organic carbon and absolute amount of nutrients) to optimize productivity in bioproducts by Aphanothece microscopica Nägeli, for further evaluation of stirring speed. The experiments were performed in a bubble column bioreactor, operating at 30ºC, pH of 7.6, C/N ratio of 20, 100 mg/L of inoculum, continuous aeration of 1 VVM (volume of air per volume of culture per minute) and absence of light. The results indicate that absolute amounts of 5000/250 using cassava starch resulted in improved system performance, reaching biomass productivity of 36.66 mg/L/h in parallel with lipid productivity of 6.65 mg/L/h. Finally, experiments with variation in stirring speed indicate that 200 rpm resulted in better average rate of substrate consumption (44.01 mg/L/h), in parallel to biomass productivity of 39.27 mg/L/h. However, the increase of stirring speed had a negative effect on lipid productivity of the process. The technological route developed indicates potential to production of biomass and bulk oil, as a result of the capacity of cyanobacteria to adapt their metabolism in varying culture conditions, which provides opportunities to modify, control and thereby maximize the formation of targeted compounds.